The zinc transporter SLC39A14/ZIP14 controls G-protein coupled receptor-mediated signaling required for systemic growth. - Shintaro Hojyo; Toshiyuki Fukada; Shinji Shimoda; Wakana Ohashi; Bum-Ho Bin; Haruhiko Koseki; Toshio Hirano (PLoS ONE, 2011)
Aberrant zinc (Zn) homeostasis is associated with abnormal control of mammalian growth, although the molecular mechanisms of Zn's roles in regulating systemic growth remain to be clarified. Here we report that the cell membrane-localized Zn transporter SLC39A14 controls G-protein coupled receptor (GPCR)-mediated signaling. Mice lacking Slc39a14 (Slc39a14-KO mice) exhibit growth retardation and impaired gluconeogenesis, which are attributable to disrupted GPCR signaling in the growth plate, pituitary gland, and liver. The decreased signaling is a consequence of the reduced basal level of cyclic adenosine monophosphate (cAMP) caused by increased phosphodiesterase (PDE) activity in Slc39a14-KO cells. We conclude that SLC39A14 facilitates GPCR-mediated cAMP-CREB signaling by suppressing the basal PDE activity, and that this is one mechanism for Zn's involvement in systemic growth processes. Our data highlight SLC39A14 as an important novel player in GPCR-mediated signaling. In addition, the Slc39a14-KO mice may be useful for studying the GPCR-associated regulation of mammalian systemic growth.